Effect of Thermal Treatment on Kelulut Honey Towards the Physicochemical, Antioxidant and Antimicrobial Properties - MARDHIAH MOHD SHAHABUDDIN; MOHD ALHAFIIZH ZAILANI; WAN ROSLINA WAN YUSOF; NOORASMIN MOKHTAR AHMAD (Borneo Journal of Resource Science and Technology, 2022)
Heat treatment on commercial honey could deteriorate its quality associated with physicochemical and bioactive capacities. In this study, the effects of thermal treatment (50 °C, 75 °C and 90 °C) on the physicochemical properties (i.e., pH, colour intensity), total phenolic content and total flavonoid content were investigated on the Kelulut honey. The results revealed a significant increase in TFC (0.154 mg QE/g honey) for the heat-treated Kelulut honey compared to the control (0.085 mg QE/g honey). The antioxidant activity of the heat-treated honey revealed an increase in 2, 2- Diphenyl-1-picrylhydrazyl levels by 42%, while the ferric reducing antioxidant power levels were reduced significantly by 22.4% compared to the untreated honey. The antimicrobial activities of heat-treated honey declined against Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Salmonella typhi bacteria at 75 °C and 90 °C. Based on the effects observed in the bioactive capacities of the heat-treated honey, it is therefore recommended to minimize thermal treatment on the honey during the processing to maintain its natural nutritional quality and benefit consumers.